KEOTENTIKAN BAHASA ARAB DALAM AL-QUR'AN: Bantahan atas Tuduhan terhadap Inkonsistensi Redaksi al-Quran - Fathin Masyhud (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2017)
This article describes the partial charges of the orientalists against the inconsistency of the Qoran followed common structure in Fusha Arabic. They alleged that the Qoran is not a holy words because it does not correspond to the correct grammar. Deviations of the Qoran to the Arabic language according to their linguistic aspects can be classified into four aspects of lexical, morphological aspects, aspects of semantic, rhetorical aspects and aspects of writing. The author presents their opinion once refutation of some scholars commentary related to the allegations.